2011
DOI: 10.1111/j.1440-169x.2011.01274.x
|View full text |Cite
|
Sign up to set email alerts
|

Robustness of the Dpp morphogen activity gradient depends on negative feedback regulation by the inhibitory Smad, Dad

Abstract: Developmental patterning relies on morphogen concentration gradients, which generally provide invariable positional information despite genetic fluctuations. Theoretical studies have predicted robust patterning; however, little experimental evidence exists to support this idea. In this report, we examine the robustness of the Decapentaplegic (Dpp) (a Drosophila homologue of bone morphogenetic protein [BMP]) activity gradient in the presence of fluctuations in Dpp receptor levels. Dpp activity can be measured b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(63 citation statements)
references
References 39 publications
(57 reference statements)
0
63
0
Order By: Relevance
“…In the absence of pent , medial-lateral diffusion of Dpp will be restricted by Dally because there is no Pent to compete for Dally binding sites (Figure 8B). The resulting high level of medially localized Dpp signaling, indicated by Mad phosphorylation (pMad) (Vuilleumier et al, 2010), has been shown to induce expression of the inhibitory Smad, daughters against dpp ( dad ), promoting a negative feedback loop to limit the range of Dpp signaling (Tsuneizumi et al, 1997; Ogiso et al, 2011). In the absence of dally , Dpp diffusion will also be restricted as Dally-binding is required to establish both Dpp and Pent gradients (Vuilleumier et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…In the absence of pent , medial-lateral diffusion of Dpp will be restricted by Dally because there is no Pent to compete for Dally binding sites (Figure 8B). The resulting high level of medially localized Dpp signaling, indicated by Mad phosphorylation (pMad) (Vuilleumier et al, 2010), has been shown to induce expression of the inhibitory Smad, daughters against dpp ( dad ), promoting a negative feedback loop to limit the range of Dpp signaling (Tsuneizumi et al, 1997; Ogiso et al, 2011). In the absence of dally , Dpp diffusion will also be restricted as Dally-binding is required to establish both Dpp and Pent gradients (Vuilleumier et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…First, we tested whether the suppression caused by RNAi for Dad , Oli , and Myc could be phenocopied with independent loss-of-function alleles for each gene (no independent alleles were available for CG10565 ). We crossed the test stock to Dad 212 (Ogiso et al 2011), Myc 2 (Maines et al 2004), Myc 4 (Pierce et al 2004), Oli Δ 9 (Oyallon et al 2012), and their respective genetic background strains at 30°. Dad 212 , Myc 4 , and Oli Δ 9 contain small deletions and are likely molecular null alleles, and Myc 2 is the result of a point mutation and is a strong, homozygous lethal allele.…”
Section: Resultsmentioning
confidence: 99%
“…This approach has been generally applied for studying the formation and robustness of morphogen gradients [17][18][19][20]26]. We use the experimental observations of the wing disc in Drosophila [28,32,35,36] to constrain and calibrate our model, which may be applied to other morphogen-mediated patterning systems.…”
Section: Mathematical Modelmentioning
confidence: 99%
“…Experimental evidence in the Drosophila wing disc reveals complex roles of the receptor in morphogenmediated patterning, in which Dfz2 (Wg receptor) broadens the range of Wg action by stabilizing it from degradation [8] and overexpressing Tkv (Dpp receptor) shrinks the Dpp gradient [27]. Both experimental [28] and theoretical [29] studies suggest that downregulation and overexpression of Tkv have crucial effects on the shape and robustness of morphogen activity.…”
Section: Introductionmentioning
confidence: 99%